Lippincott's clinical skill series surgical care set - Conaway, Deborah Jean; Studio Three Productions (Philadelphia : Lippincott's-Raven, 1997)
This video series offers essential guidence and detailed, up-closed demotrations of clinical skill used by nurse and other health care providers.
Videocassettes is available at Koleksi Media Perpustakaan HUKM
j.1-Providing wound care; j.2-Implementing postoperative care; j.3-Implementing preoperative care
Technical consultant, Deborah Jean Conaway
Keywords: Surgical Wound Infection -- nursing -- videocassettes; Drainage -- nursing -- videocassettes; Perioperative Nursing -- methods -- videocassettes; Preoperative Care -- nursing -- videocassettes; Postanesthesia Nursing -- methods -- videocassettes